Mengukur Prestasi Belajar Pendidikan Agama Islam Siswa SMP dalam Perspektif Gender - Lathifatul Izzah; Arif Rahman Hakim (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
This study aims to prove that gender does not affect the learning achievement of Islamic education and character of junior high school students. The construct in society is that men are superior to women. Men are smarter than women. The problem solving in this research uses quantitative research with comparative analysis. In this study, the authors used data collection techniques in the form of conventionalized results of Mid-Semester Assessment (PTS) and Final Semester Assessment (PAS). The results showed the mean score of male students in the Islamic Religious Education subject was 81.51 with a standard deviation of 6.863 with a total range of 27. The lowest score for male students was 68 and the highest score was 95. The majority of male students scored category is quite good (C) or a value of 75 - 83, that is, there are 25 students or 47.2% of the 53 male students. The average achievement score of female students in the subject of Islamic Religious Education has an average of 85.57 with a standard deviation of 7.324, a total range of 28, the lowest score is 71 and the highest score is 99. The majority of students scored quite well, between scores of 75 -83, namely as many as 20 students or 37.7% of 53 female students. In the independent t test it is known that the sig (2 tailed) value of 0.29 and> 0.05, from these results it shows that Ho is accepted and Ha is rejected, meaning that there is no positive and significant difference between male and female students to get achievement. learn Islamic religious education